Meeting Household Energy Needs through Community Forestry: A Systematic Review of Evidence from Nepal - Prem Bahadur Giri; Dr. Hari Prasad Ghimire; Bijay Raj Giri; Trilochana Pokhrel, (Indian Journal of Energy and Energy Resources (IJEER), 2025)
The availability of clean and affordable household energy has been long-standing in rural Nepal, with household biomass sources taking over the household consumption. This paper examines the role of community forestry in providing households with energy security, promoting social inclusion, and sustaining the environment. The review uses a systematic approach guided by the PRISMA 2020 standards and synthesises the evidence from 92 empirical studies on the issue published since 2004. Web of Science, Scopus, and NepJOL were used to gather data based on inclusion criteria for community forestry, household access to energy, and participatory governance. The conceptual framework used to evaluate the interaction between human, natural, social, financial, and physical capitals and governance systems to determine household energy outcomes was the Sustainable Livelihoods Approach (SLA). Results indicate that community forests are the primary source of fuelwood and other forest products for 6090 per cent of rural households, cut household energy costs by up to 18 per cent, and enhance forest restoration in 85 per cent of the studies examined. This improves transparency and meaningful representation, as well as forest conditions and biodiversity. Nevertheless, inequities include elite capture, the underrepresentation of women and marginalised groups, and poor uptake of cleaner technologies, which hinder equal gains. The findings highlight that community forestry contributes substantially to the welfare of rural communities. Still, sustainable energy transitions require reforming policies to set energy targets in forestry strategies, advance alternative energy technologies, and enhance intergovernmental coordination under federal governance. The study finds that incorporating household energy objectives into community forestry policies is essential for achieving the Nepal Sustainable Development Goals (SDGs 7, 13, and 15). It suggests an adaptive governance system, participatory governance, and technology-based interventions to fast-track the transition of the rural energy system toward cleaner, more equitable systems.